Metal-Free Selective Air-Oxidation of Sulfides to Sulfoxides Using 2,2′-Azobis-(2,4-dimethyl-4-methoxyvaleronitrile) (V-70) and Isobutyraldehyde - Kato, Yamato; Kanoh, Miho; Shioiri, Takayuki; Matsugi, Masato (Synlett, 2024)
Selective oxidation of sulfides to sulfoxides using ‘air’ was achieved using a combination of 2,2′-azobis-(2,4-dimethyl-4-methoxyvaleronitrile) (a radical initiator) and isobutyraldehyde (a co-oxidant). Various sulfides were successfully converted into their corresponding sulfoxides using this method. This approach promotes a sustainable oxidation process by excluding harmful oxidants, such as peroxides and metal reagents.
Keywords: air; oxidation; V-70; radicals; sulfoxide